Conductive particles, anisotropic conductive material, and method for producing conductive particles

By attaching insulating particles and a hydrophobic surface treatment layer to the surface of conductive particles, the problem of aggregation between conductive particles is solved and the manufacturing of anisotropic conductive materials with low defect rates is achieved.

CN119339989APending Publication Date: 2025-01-21DUK SAN NEOLUX
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410972453.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-20
Filing Date
2024-07-19
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the process of manufacturing anisotropic conductive materials, aggregation is prone to occur between conductive particles, resulting in product defects, and existing wet adhesion methods are difficult to avoid aggregation problems.

Method used

By forming insulating particles and a hydrophobic surface treatment layer on the surface of the conductive particles, the chemical bonding force of the first substituent and the second substituent is used to prevent the insulating particles from combining with the conductive layers of other conductive particles, thereby avoiding aggregation.

Benefits of technology

It is realized that aggregation between conductive particles does not occur during the manufacturing process of anisotropic conductive materials, which reduces the product defect rate and improves the reliability of conductive materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119339989A_ABST
    Figure CN119339989A_ABST
Patent Text Reader

Abstract

The invention relates to conductive particles, an anisotropic conductive material, and a method for producing conductive particles. Conductive particles are dispersed in a resin composition of an anisotropic connection material containing a binder resin and a solvent, including: a core; a conductive layer disposed on the core, the conductive layer comprising a metal; insulating particles provided on the conductive layer, the insulating particles being connected by a first substituent bonded to the metal of the conductive layer, and being provided in the first region of the conductive layer; the hydrophobic surface treatment layer is arranged on the conductive layer, is connected with the conductive layer through a second substituent group combined with the metal of the conductive layer, and is arranged in the second area of the conductive layer; the first region and the second region are not overlapped.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a conductive particle with insulating particles, in particular to a conductive particle conductive material and a connection structure used for electrical connection in anisotropic conductive materials. Background Art

[0002] Conductive particles are used as conductive connecting materials in anisotropic conductive materials, such as anisotropic conductive film, anisotropic conductive adhesive, anisotropic conductive paste, anisotropic conductive ink and anisotropic conductive sheet.

[0003] When conductive particles are used in anisotropic conductive materials, they are usually mixed with a curing agent, a binder, a resin binder, etc., and the electrical connection between the upper and lower electrodes is maintained by curing / bonding of the anisotropic conductive material after pressurization / heating.

[0004] In particular, anisotropic conductive film (ACF) is mainly used in COG (Chip on Glass), FOG (Film on Glassboard), and FOB (Film on Board). COG refers to connecting the driver IC chip and the organic substrate, FOG refers to connecting the flexible substrate and the organic substrate, and FOB refers to connecting the flexible substrate and the epoxy substrate to achieve the exchange of electrical signals.

[0005] On the other hand, as the display resolution increases, the electrode pitch becomes smaller. When the electrode pitch is narrow, when connecting the electrodes between the chip and the substrate, due to the flow of the ACF resin, some conductive particles will flow with the ACF resin, causing the conductive particles to connect the adjacent electrodes on the left and right, resulting in a short circuit between the adjacent electrodes.

[0006] In order to solve this problem, a method of forming an insulating layer on the surface of conductive particles has been proposed. The insulating layer can be formed by coating an insulating material or attaching insulating particles to the surface of conductive particles. The former has good insulating properties, but it will significantly increase the connection resistance between the upper and lower electrodes, and it is difficult to ensure a uniform coating; the latter, although it is easy to fall off, has lower connection resistance and excellent inter-particle insulation properties than the insulating layer coating method, and has therefore been widely used in recent years.

[0007] Therefore, the method of attaching insulating particles to the surface of conductive particles generally adopts a wet attachment method, that is, a solvent, conductive particles and insulating particles are mixed and dispersed before attachment.

[0008] However, conductive particles with insulating fine particles attached using a wet attachment method are prone to aggregation problems in ACF resin.

[0009] Aggregation of insulating conductive particles in ACF can lead to product defects, making it very difficult to manufacture ACF using insulating conductive particles.

[0010] Prior art literature

[0011] Patent Literature

[0012] (Patent Document 1) Japanese Patent Publication No. 23105861 (2011.06.02) Summary of the invention

[0013] Issues to be resolved

[0014] The technical problem to be solved by the embodiments of the present invention is to provide conductive particles, anisotropic conductive materials and connection structures that do not cause aggregation between conductive particles during the process of manufacturing anisotropic conductive materials, and have insulating particles attached to their surfaces by solving the problems in the prior art.

[0015] Solution to the problem

[0016] The conductive particle according to the first aspect of the present invention is a conductive particle dispersed in a resin composition of an anisotropic connecting material including a binder resin and a solvent, comprising: a core; a conductive layer disposed on the core, comprising a metal; insulating particles disposed on the conductive layer, the insulating particles being connected via a first substituent bonded to the metal of the conductive layer and disposed in a first region of the conductive layer; and a hydrophobic surface treatment layer disposed on the conductive layer, the hydrophobic surface treatment layer being connected via a second substituent bonded to the metal of the conductive layer and disposed in a second region of the conductive layer;

[0017] The first region and the second region do not overlap.

[0018] In addition, the height of the insulating fine particles may be 100 nm to 300 nm.

[0019] Furthermore, the first substituent is preferably at least one selected from the group consisting of an hetero group, an ether group, a carbonate group and a hydroxyl group, and the second substituent is preferably at least one selected from the group consisting of a thiol group, a phosphoric acid group and a phosphoric acid ester group.

[0020] The conductive layer of the conductive particles may further include protrusions, and in this case, the insulating particles may be formed on the protrusions.

[0021] Furthermore, a surface treatment layer may also be formed on the protrusions.

[0022] Furthermore, the diameter of the insulating fine particles is preferably larger than the height of the protrusions.

[0023] The anisotropic conductive film according to the second aspect of the present invention is an anisotropic conductive film made of conductive particles, and when observed with an optical microscope, the conductive particles are 2 The number of aggregated particles consisting of five or more conductive particles is less than 0.2 ppm on an area.

[0024] A method for producing conductive particles according to another aspect of the present invention comprises:

[0025] Core provision step;

[0026] a conductive layer forming step of forming a conductive layer with or without protrusions on the core;

[0027] An insulating particle attaching step of mixing a solution containing insulating particles and a first substituent of a solvent with the conductive particle intermediate produced in the conductive layer forming step to attach the insulating particles to the first region of the conductive particle intermediate;

[0028] After the insulating fine particle attaching step, a surface treatment step of mixing a surface treatment material including a second substituent to form a surface treatment layer on a second region of the conductive layer different from the first region; and

[0029] The surface treatment step is followed by a drying step.

[0030] At this time, the thickness of the conductive layer in the conductive layer forming step may be 80 nm to 400 nm.

[0031] Furthermore, the drying step is preferably performed at 100°C to 200°C.

[0032] Furthermore, in the insulating fine particle attaching step, the weight ratio of the insulating fine particles relative to the total area of ​​the outer surface of the conductive layer is preferably 5% to 40%.

[0033] Effects of the Invention

[0034] According to the conductive particles of the embodiments of the present invention, the reactivity between the insulating particles attached to the surface of the conductive particles and other conductive particles is reduced, and the conductive particles are prevented from adhering to each other when the conductive particles are dried and during the manufacturing process of the anisotropic conductive material, thereby manufacturing anisotropic conductive materials and connection structures with low defect rates. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a photograph of the dispersion of insulating conductive particles used in the embodiment of the present invention in the ACF.

[0037] Figure 2 This is a photograph of the dispersion of insulating conductive particles in ACF used for comparison.

[0038] Figure 3 This is a SEM photograph of conductive particles with insulating particles attached. DETAILED DESCRIPTION

[0039] Before describing the present invention in detail, it should be understood that the terms used in this specification are only used to describe specific embodiments, rather than to limit the scope of the present invention, which is only defined by the appended claims. All technical and scientific terms used in this specification, unless otherwise specified, have the same meaning as those commonly understood by those skilled in the art.

[0040] Throughout the specification and claims, unless otherwise stated, the terms “comprise”, “comprises” and “comprising” mean including the stated items, steps or a collection of items and steps, and do not exclude any other items, steps or a collection of items and steps.

[0041] Furthermore, various embodiments of the invention may be combined with other embodiments unless expressly stated to the contrary. Any feature described as being preferred or advantageous may be combined with any other feature described as being preferred or advantageous.

[0042] First aspect: conductive particles

[0043] The conductive particle according to the embodiment of the present invention includes a core, a conductive layer disposed on the core, insulating particles disposed on the conductive layer, and a surface treatment layer.

[0044] The core is an insulating bead having very low electrical conductivity, which may be made of resin particles or an organic / inorganic mixture, used in anisotropic conductive materials, and made of a material that does not break when electrically connected. That is, when the conductive particles according to the embodiments of the present invention are subjected to force within the range of electrical connection between electrodes, the insulating beads inside the conductive particles will deform but will not break.

[0045] When the core is made of resin particles, the resin particles can use at least one copolymer selected from carbamate, styrene, acrylate, benzene, epoxy, amine and imide monomers or their modified monomers or mixtures of these monomers, prepared by seed polymerization, dispersion polymerization, suspension polymerization or emulsion polymerization.

[0046] When the core is made of an organic / inorganic mixture, a core-shell structure is preferred. If the core is an organic substance, the shell is an inorganic substance; if the core is an inorganic substance, the shell is an organic substance.

[0047] At this time, the organic substance may be a polymer using the aforementioned monomer or a modified monomer or a mixed monomer; the inorganic substance may be an oxide (such as SiO2, TiO2, Al2O3 and ZrO2); a nitride (such as AlN, Si3N4, TiN and BaN); or a carbide (such as WC, TiC and SiC). The method of forming the shell includes a chemical coating method, a sol-gel method, a spraying method, a CVD (chemical vapor deposition), a PVD (physical vapor deposition) and electroplating.

[0048] The conductive layer is a layer that imparts conductivity to the conductive particles. The material of the conductive layer of the conductive particles is not limited, but can be composed of one or more elements such as P, B, Cu, Au, Ag, W, Mo, Pd, Co, Pt, etc. based on Ni. For example, the material of the conductive layer can be composed of an alloy composition such as Ni-P, Ni-B, Ni-W, Ni-Mo, Ni-Co, etc. Alternatively, the material of the conductive layer can be composed of two alloy compositions such as Ni-P-Pd, Ni-B-Pd, Ni-P-Co, Ni-B-Co, Ni-PW, Ni-BW, etc. Alternatively, the material of the conductive layer can be composed of three alloy compositions such as Ni-P-Co-Mo, Ni-B-Co-Mo, Ni-P-Pd-W, Ni-B-Pd-W, etc. In addition, the material of the conductive layer can also be composed of more than four alloy compositions. In addition, the conductive layer can be a multilayer alloy layer composed of alloy elements.

[0049] The thickness of the conductive layer of the conductive particles is preferably 80nm to 400nm. If the thickness of the conductive layer is less than 80nm, the resistance will increase during electrical connection; if it exceeds 400nm, under the heating / pressurization connection conditions of the anisotropic conductive material, even if the conductive particles are slightly deformed, peeling will occur between the conductive layer and the insulating beads, reducing the reliability of the product. A more preferred thickness is 90nm to 300nm. The most preferred thickness is 100nm to 250nm.

[0050] The outer surface of the conductive layer of the conductive particles can be provided with a noble metal layer containing noble metals such as gold, silver, platinum or palladium. The noble metal layer can improve the conductivity of the conductive particles and prevent oxidation. The method for forming the noble metal layer in the present invention is not limited, and conventional techniques such as sputtering, electroplating, and deposition can be used.

[0051] In order to more easily penetrate the oxide film of the electrode, protrusions may be formed on the surface of the conductive particles. The shape of the protrusions of the conductive particles in the present invention is not limited. They may be spherical, elongated, or aggregated. The most preferred protrusion shape is a gradually narrowing shape.

[0052] The method for forming the protrusions on the surface of the conductive particles is not limited. The protrusions can be formed integrally with the conductive layer, or the conductive layer can be formed after nano-sized particles are attached to the core, or a first conductive layer is formed on the core, nano-sized particles are attached, and then a second conductive layer of the same or different material as the first conductive layer is formed.

[0053] The size of the protrusion is not limited, but is preferably 50 nm to 500 nm, more preferably 100 nm to 350 nm.

[0054] The insulating particles are particles formed on the first region of the conductive layer to prevent short circuits between the conductive particles and adjacent electrodes when the conductive particles are used as anisotropic conductive materials. If there are protrusions, the insulating particles may also be formed on the protrusions.

[0055] The material of the insulating particles can be insulating resin particles or inorganic particles. The resin particles can be selected from a polymer containing at least one styrene or acrylate or methacrylate selected from an alkyl group containing at least one carbon atom and a diacrylate or dimethacrylate at both ends of ethylene glycol containing at least one carbon atom. The inorganic particles can contain one or more materials selected from a trimethoxysilane series containing acryl, phenyl, and vinyl.

[0056] In order to exhibit an insulating effect, the particle size may be 90 nm or more, but in order to ensure sufficient connection resistance and insulation resistance, the size is preferably 100 nm to 300 nm, and more preferably 100 nm to 250 nm.

[0057] In order to improve the insulation and conductivity effects, insulating particles of different sizes can be mixed, and organic / inorganic particles can also be mixed.

[0058] In order to attach the insulating particles to the surface of the conductive particles, a wet attachment method is used to mix and attach the solvent, the conductive particles and the insulating particles. The insulating particles are attached to the conductive layer or the protrusions via a polymer having a first substituent having a metal bonding force with the conductive layer.

[0059] The first substituent is any heteroatom or substituent that has a chemical bonding force such as a covalent bond or a polar bond to the metal, or has a strong affinity to the metal so that it can be physically adsorbed and fixed on the metal surface. Specifically, the first substituent can be selected from the group consisting of an hetero group, an ether group, a carbonate group, and a hydroxyl group, wherein the hetero group preferably contains at least one element selected from the group consisting of sulfur, phosphorus, nitrogen, and oxygen.

[0060] The insulating particles are preferably attached to 5% to 40% of the total area of ​​the outer surface of the conductive layer (including the outer surface of the protrusions). If the attached area is less than 5%, the insulating effect is insufficient; if it exceeds 40%, there are too many insulating particles, resulting in an increase in connection resistance. A portion of the outer surface of the conductive layer of the conductive particles remains exposed.

[0061] The surface treatment layer is a layer that prevents the insulating particles on the conductive layer from combining with the insulating particles attached to the conductive layer of other conductive particles, and is formed on the second region of the conductive layer but not on the first region where the insulating particles are formed.

[0062] That is, the surface treatment layer has a substance that can react and bond with the metal of the conductive layer of the conductive particles, so that the surface treatment layer can be prevented from being easily separated from the second region, and the chemical reaction with the insulating particles is small. This is because if the surface treatment layer is also formed on the surface of the insulating particles, in the subsequent drying process, the surface area of ​​the surface treatment substances formed on the conductive layers of other conductive particles that react with each other will increase, resulting in a large number of aggregated insulating conductive particles.

[0063] The material forming the surface treatment layer may use a substituent having hydrophobic characteristics and capable of bonding to metal, that is, a compound containing a hydrophobic hydrocarbon chain having 3 or more carbon atoms and at least one substituent selected from the group consisting of thiol, phosphate and phosphate ester groups.

[0064] The above-mentioned hydrophobic hydrocarbon chain with 3 or more carbon atoms may specifically use a fatty acid series, a series of substances having an alkyl group or a phenolic group, and these substances may more specifically contain an alkyl group with 6 to 60 carbon atoms, a cycloalkyl group with 6 to 60 carbon atoms, an aryl group with 6 to 60 carbon atoms, an aralkyl group with 7 to 60 carbon atoms, an alkyl ether group with 3 to 60 carbon atoms, or a substance containing two or more chain structures of the above-mentioned substances.

[0065] Second aspect: Method for manufacturing conductive particles

[0066] The method for producing conductive particles according to an embodiment of the present invention includes a core providing step (S1), a conductive layer forming step (S2), an insulating particle attaching step (S3), a surface treatment step (S4) and a drying step (S5).

[0067] At this time, the core providing step (S1) includes a core particle synthesizing step (S1a) and a plating catalyst activating step (S1b).

[0068] The core particle synthesis step (S1a) is a step of using monomers such as carbamate, styrene, acrylate, benzene, epoxy, amine, and imide, or modified monomers of these monomers, or mixed monomers of the above monomers, to polymerize by seed polymerization, dispersion polymerization, suspension polymerization, emulsion polymerization, etc. to produce a copolymer, thereby producing a core.

[0069] When the core is a mixed particle, if the core has a core-shell structure, when the core is an organic matter, the shell is an inorganic matter; when the core is an inorganic matter, the shell is an organic matter. The organic matter used here is the above-mentioned monomer, modified monomer or mixed monomer, and the inorganic matter used can be oxides including SiO2, TiO2, Al2O3 and ZrO2, nitrides including AlN, Si3N4, TiN and BaN, and carbides including WC, TiC and SiC.

[0070] The shell can be formed by a chemical coating method, a sol-gel method, a spray coating method, a CVD (chemical vapor deposition method), a PVD (physical vapor deposition method), an electroplating method, or the like.

[0071] In addition, a form in which inorganic particles are dispersed in an organic matrix, a form in which organic particles are dispersed in an inorganic matrix, and a form in which organic / inorganic substances are dispersed in a 50:50 ratio are also possible.

[0072] For example, as the organic substance, ethoxylated triacrylate monomer and ethoxylated diacrylate monomer are used, and they are mixed with a solvent and a polymerization initiator to form a solution for dispersion treatment. At this time, the dispersion treatment may include a homogenizer treatment using ultrasonic waves.

[0073] Furthermore, after adding a solution containing a dispersion stabilizer and a surfactant to the above-mentioned dispersion treatment liquid, a polymerization treatment is performed under elevated temperature conditions to form nuclei.

[0074] Next, in the plating catalyst activation step (S1b), the core particles previously manufactured in the S1a step are activated without plating catalyst. At this time, the plating catalyst used in the plating catalyst activation step (S1b) can be replaced by attaching small metal or inorganic particles to insulating particles if it can provide similar effects.

[0075] Specifically, the plating catalyst activation step (S1b) is to treat the surface of the core particles with a surfactant, then perform sensitization treatment using a non-plating catalyst, and after pre-treatment by various known methods, place the sensitized core particles into a solution containing a non-plating catalyst precursor for activation treatment.

[0076] The activated core particles are placed in a solution containing a strong acid and stirred at room temperature for acceleration treatment, thereby obtaining catalytically treated core particles for electroless plating.

[0077] Next, the conductive layer forming step ( S2 ) having protrusions includes a core dispersing step ( S2 a ) and a conductive layer forming step ( S2 b ).

[0078] The core dispersion step (S2a) is to put the core into an alloy plating solution for forming a conductive layer for dispersion. The alloy plating solution is prepared by dissolving a precursor of an alloy element, a complexing agent, lactic acid, a stabilizer, and a surfactant in sequence.

[0079] The catalytically treated core particles obtained in the above step (S1b) are added to the prepared electroplating solution, and dispersed using an ultrasonic homogenizer.

[0080] It is ideal to adjust the pH of the dispersion treatment liquid to 5.5-6.5 using an alkaline solution such as ammonia water, because this can improve the adhesion and dispersibility of the insulating particles to the conductive layer during the initial Ni reduction reaction in the conductive layer formation step (S2b) described later. If the pH of the dispersion treatment liquid is lower than 5.5, for example, below pH 4, although the adhesion and dispersibility are good, the reactivity is too low and some particles may not be plated; and when the pH exceeds 6.5, the conductive layer surface is loosely formed due to abnormal Ni deposition, and the adhesion and dispersibility will deteriorate.

[0081] Next, the cores put into the electroplating solution after the dispersion treatment are processed to form a conductive layer (S2b). At this time, the number of layers, materials, formation methods or protrusion formation methods of the conductive layer are not limited. The thickness of the conductive layer is formed to be 80nm to 400nm, and the protrusion can be formed integrally with the conductive layer or formed separately. For example, the protrusion can be grown integrally with the conductive layer, or a conductive layer can be formed after nano-sized particles are attached to the core, or nano-sized particles are attached after a first conductive layer is formed on the core, and then a second conductive layer of the same or different material as the first conductive layer is formed to form the protrusion.

[0082] An example of the integrated formation of the protrusion and the conductive layer is that in the core dispersion step (S2a), one or more precursors selected from P and B are added to the above-mentioned nickel-based alloy electroplating solution, and then in the step of forming the conductive layer with the protrusion (S2b), the precursors of one or more elements selected from Cu, Au, Ag, W, Mo, Pd, Co, and Pt are added to the electroplating solution after the dispersion treatment to form a protruding conductive layer with a concentration gradient.

[0083] At this time, the alloying elements added in batches can be added in 2 to 5 times every 10 minutes to 30 minutes, or can be added in 2 to 4 times every 15 minutes to 25 minutes. In this process, the amount added can be gradually increased, or added continuously as needed, and the addition speed should be such that the amount added in each time period is gradually increased, so as to gradually increase the concentration of the alloying elements on the surface of the conductive layer from the direction of the protruding end.

[0084] When the concentration of the alloy element gradually increases from the end of the protrusion on the surface of the conductive layer, the contact resistance during connection can be reduced, thereby improving the reliability of the connection.

[0085] The pH value of the plating solution before and after the batch addition should be maintained within the control range according to the type of alloying elements added when forming the raised conductive layer. For example, when adding the precursor of P, the pH value should be maintained in the range of 5.5-6.0; when adding the precursor of B, the pH value should be maintained in the range of 8.5-9.0. At this time, if the pH value of the plating solution is too low, the chemical reactivity is low, which will cause the problem of protrusion formation; on the contrary, if the pH value is too high, it will cause abnormal excessive deposition of the conductive layer, destroy the balance of the plating solution, and produce poor electroplating.

[0086] Furthermore, applying elevated temperature conditions can avoid abnormal deposition in the bulge formation mechanism, thereby forming bulges of the desired structure, which is more ideal.

[0087] The insulating fine particle adhering step (S3) is a step of adhering the insulating fine particles to the conductive layer. There are two methods for adhering the insulating fine particles to the surface of the conductive particles: a dry method and a wet method, but the wet method is preferably used in this embodiment. The dry method is a method of physically colliding the insulating fine particles onto the surface of the conductive particles at a high temperature for adhesion, and it is difficult to achieve uniform particle adhesion.

[0088] The wet method is a method of adhering a solvent, conductive particles and insulating particles mixed in a solvent, and the insulating particles are adhered to the conductive layer or the protrusion by providing a substituent reactive with the conductive layer metal of the conductive particles on the surface of the insulating particles. That is, the surface of the insulating particles has a substituent that enhances the reactivity of the conductive layer of the conductive particles or the metal on the surface of the protrusion. Such a substituent can be selected from the group consisting of an assorted group, a thiol group, a carbonic acid group and a hydroxyl group. The assorted group preferably contains a substance of at least one element selected from the group consisting of sulfur, phosphorus, nitrogen and oxygen.

[0089] On the other hand, not only the insulating particles but also the conductive particles may have substituents on their surfaces. In this case, the substituents on the insulating particles and the substituents on the conductive particles preferably have a high binding force.

[0090] In the wet method, the insulating particles are not formed on the entire surface area of ​​the conductive particles, but preferably formed on 5 to 40% of the total area of ​​the outer side of the conductive layer (including the protrusions if any). This is because the insulating particles have a surface affinity with the conductive particle surface, so the insulating particles have a low tendency to adhere to each other. Therefore, part of the conductive particle surface is open and the conductive layer is exposed.

[0091] At this time, the area occupied by the insulating particles in the total area of ​​the outer side surface of the conductive layer can be calculated by the following formula 1 by photographing the surface of the conductive particles to which the insulating particles are attached through SEM.

[0092] (Formula 1)

[0093] The attached area of ​​insulating particles (%) = ((unit surface area of ​​insulating particles × number of attached insulating particles) / total surface area of ​​conductive particles) × 100%

[0094] On the other hand, in order to improve the insulation and conductivity effects, insulating particles of different particle sizes can be mixed and used, and organic / inorganic particles can also be mixed and used.

[0095] In order to make the insulating particles adhere better to the surface of the conductive particles, there are substituents not only on the surface of the insulating particles but also on the surface of the conductive particles, which can increase the adhesion of the insulating particles and the adhesion area of ​​the insulating particles on the conductive particles.

[0096] The surface treatment step (S4) is a step of introducing a surface treatment layer on the surface of the conductive particles to which the insulating particles are attached in order to solve the problem of aggregation between the conductive particles when the insulating particles are attached.

[0097] Generally speaking, the wet method can achieve uniform particle attachment, but the conductive particles need to be dried afterwards. At this time, aggregation between the conductive particles attached with insulating particles may occur during the drying process. It is speculated that this aggregation occurs because the metal-affinity substituents contained in the insulating particles tend to attach to the conductive layers of other conductive particles. That is, during the drying process, the substituents of the insulating particles will attach to the surfaces of the conductive particles of other conductive particles to which the insulating particles are not attached. After drying, as time passes, the adjacent conductive particles and the insulating particles will naturally adhere to each other, and ultimately, multiple particles will aggregate when the ACF is manufactured. Therefore, according to this embodiment, after the insulating particles are attached, the surface of the conductive particles exposed by the conductive layer of the conductive particles, that is, the portion to which the insulating particles are not attached, is subjected to a hydrophobic surface treatment.

[0098] As the substance forming the surface treatment layer, there can be used a compound containing at least one substituent selected from the group consisting of a thiol group, a phosphate group and a phosphate ester group, having hydrophobic characteristics and capable of bonding to a metal, and a compound containing a hydrophobic hydrocarbon chain having 3 or more carbon atoms.

[0099] The hydrophobic hydrocarbons having 3 or more carbon atoms may specifically use fatty acid series, series of substances having alkyl or phenol groups, and these substances may more specifically contain alkyl groups having 6 to 60 carbon atoms, cycloalkyl groups having 6 to 60 carbon atoms, aryl groups having 6 to 60 carbon atoms, aralkyl groups having 7 to 60 carbon atoms, alkyl ether groups having 3 to 60 carbon atoms, or substances containing chain structures of two or more of the above substances.

[0100] The drying step (S5) is a step of drying the conductive particles produced by the wet process. The drying temperature varies depending on the type of solvent, but is preferably performed at 100°C to 200°C.

[0101] The drying step is because the conductive particles and the solvent are in a mixed state when the insulating fine particles are wet-attached to the conductive particles. Therefore, in order to obtain the desired conductive particle density and connection resistance by inputting a certain amount when manufacturing the anisotropic conductive material, a step of drying the solvent is required.

[0102] In the drying step of the present invention, as mentioned above, due to the formation of the surface treatment layer, the substituents of the attached insulating particles will hardly cause the insulating particles on the surface of the conductive particles to adhere to the surface of the conductive particles (conductive layer) to which the insulating particles are not attached during the drying process. After drying, the adjacent conductive particles will not naturally adhere to the insulating particles over time. As a result, multiple particles will not aggregate when manufacturing ACF.

[0103] That is, a surface treatment layer having hydrophobic characteristics and a substituent capable of bonding with metal is formed on the outer side of the conductive layer of the conductive particle to prevent the insulating particles from adhering to the conductive layer of other conductive particles. At the same time, the surface treatment layer is not formed on the outer side of the insulating particles to prevent the surface treatment materials from reacting with each other when the surface treatment layer is formed on the entire outer side of the conductive particle, resulting in a large number of aggregated insulating conductive particles.

[0104] Aspect 3: Anisotropic Conductive Materials

[0105] The conductive particles according to the present invention are dispersed in a resin binder to produce anisotropic conductive materials, such as anisotropic conductive pastes, anisotropic conductive films and anisotropic conductive sheets. The conductive particles are uniformly dispersed in a resin binder and then used as anisotropic conductive paste or coated on a release paper surface to form an anisotropic film.

[0106] At this time, the resin binder is not limited, for example, the resin binder can be a vinyl resin such as styrene, acrylic acid, vinyl acetate, a thermoplastic resin such as polyolefin, polyamide, a curing resin such as urethane, epoxy, etc. The resin can be used alone or in combination of two or more. In particular, the resin binder preferably contains a monomer similar to the aforementioned core so as to exhibit similar behavior when the temperature environment changes.

[0107] Free radical initiators such as benzoyl peroxide (BPO) and photoinitiators such as trimethylbenzoylphenylphosphonate (TPO) and epoxy latent curing agents such as HX3941HP may be used alone or in combination to polymerize or cure in a resin binder.

[0108] In addition, other substances may be added to the resin binder within the scope that does not hinder the achievement of the purpose of the present invention. For example, at least one of a colorant, a plasticizer, a heat stabilizer, a light stabilizer, an antioxidant, and inorganic particles may be further added.

[0109] Fourth aspect: connecting structure

[0110] The conductive particles used in the present invention are not limited to any specific use, structure or material. That is, the connection structure connects circuit boards by using the conductive particles or anisotropic conductive materials of the present invention. For example, it can be used to electrically connect a display driver IC and an FPC. The connection structure prevents short circuits between left and right electrodes during connection, thereby preventing circuit malfunctions.

[0111] Example

[0112] Example 1

[0113] Insulation particle synthesis steps:

[0114] Acrylamide 13.5g, polyvinyl pyrrolidone (PVP) 108g, ethanol (Ethanol) 400g, deionized water (DIW) 3500g were mixed into a first solution, poured into a 5L reactor, and stirred at 150rpm for 30 minutes using a magnetic stirrer to dissolve. Styrene 125g, butyl acrylate 13.5g, ethylene glycol dimethacrylate (EGDMA) 15g were mixed into a second solution, placed in a 250mL beaker, ultrasonically treated for 10 minutes to dissolve, and then poured into the first solution in the 5L reactor. Then, the 5L reactor was placed in a water bath and heated from room temperature to 75°C at 250rpm for 1 hour. Potassium persulfate (KPS) 1.1g and deionized water (DIW) 50g were mixed into a third solution, placed in a 100mL beaker, ultrasonically treated for 10 minutes to dissolve, and then poured into the first and second solutions maintained at 75°C. After the third solution was added, the reaction was maintained at 75°C for 12 hours to complete the polymerization reaction. After the reaction was completed, it was naturally cooled to room temperature, and then the aggregates were removed through a 250-mesh sieve. The insulating particles were washed and purified by methanol for 3 times to prepare a solution with a weight ratio of 5wt%.

[0115] The size of the prepared insulating fine particles was measured using a field emission scanning electron microscope (FE-SEM) and was 110 nm. The glass transition temperature (Tg) of the insulating fine particles was measured using differential scanning calorimetry (DSC) and was 110°C.

[0116] Insulation particle attachment steps:

[0117] The insulating particles dispersed in methanol were dispersed by ultrasonic treatment for 10 minutes. Then 100g of conductive particles were added to a 2L reactor, and 600g of methanol were added. The conductive particles used were PN-T3.25R from Tokuyama High-Tech Metals Co., Ltd. The size of the conductive particles was 3.25μm and there were protrusions on the surface. The 2L reactor was placed in an ultrasonic bath maintained at 65°C, and the insulating particles dispersed in methanol were added so that the insulating particles reached 10% of the weight of the conductive particles, that is, 10g of the dispersed solution of insulating particles was added, and ultrasonic treatment was performed at 250rpm for 1 hour to attach the insulating particles.

[0118] After the attachment was completed, the reactor was cooled naturally, and when the temperature of the ultrasonic bath dropped below 40°C, the reactor was taken out of the ultrasonic bath, and the insulating conductive particles were washed 3 times and purified 3 times using methanol. The attachment of the insulating particles was confirmed using a field emission scanning electron microscope (FE-SEM).

[0119] Surface treatment steps:

[0120] Add 50g of undried conductive particles with insulating particles to 600g of ethanol and prepare a 2L reactor. After stirring the 2L reactor for 10 minutes, add bis(2-ethylhexyl)phosphate equivalent to 1wt% of the conductive particles with insulating particles, then put the beaker into an ultrasonic bath at 60°C and perform ultrasonic treatment for 30 minutes. The reaction is terminated when it is naturally cooled to 30°C, washed with methanol 3 times, and purified 3 times. Use a spray dryer to dry the purified insulating conductive particles. Use a field emission scanning electron microscope (FE-SEM) to confirm the insulating particle adhesion of the dried conductive particles.

[0121] Anisotropic conductive film manufacturing steps:

[0122] 2g of acrylic resin W116.3 (trade name manufactured by Negami Chemical), 20g of phenoxy resin (trade name manufactured by TotoKasei), 15g of acrylic epoxy resin VR-60 (trade name manufactured by Showa Denko), 0.5g of thermal initiator BPO, 0.5g of LPO, and 5g of epoxy silane coupling agent A-187 (trade name manufactured by Momentive) were mixed and a mixture with a solid content of 50% was prepared using solvent toluene. Insulated treated conductive particles were added at a ratio of 8000 per square millimeter, and then mixed for 5 minutes using a planetary mixer at a revolution of 400 rpm and a rotation of 150 rpm, and mixed 3 times in total to prepare an anisotropic conductive paste. The anisotropic conductive paste was coated on a release film with a coating thickness of 12 μm, and dried with hot air at 75°C for 5 minutes to prepare an anisotropic conductive film (ACF) with a final thickness of 6 μm.

[0123] <Example 2>

[0124] Conductive particles and an anisotropic conductive film were manufactured in the same manner as in Example 1, except that 1200 g of ethanol was used to synthesize insulating fine particles having a size of 150 nm and a glass transition temperature (Tg) of 110°C.

[0125] <Example 3>

[0126] Conductive particles and anisotropic conductive films were manufactured in the same manner as in Example 1, except that 54 g of polyvinyl pyrrolidone (PVP), 1200 g of ethanol, and 0.8 g of potassium persulfate (KPS) were used to synthesize insulating particles with a size of 220 nm and a glass transition temperature (Tg) of 110°C.

[0127] <Example 4>

[0128] Conductive particles and an anisotropic conductive film were prepared in the same manner as in Example 1, except that 1200 g of ethanol and 22.5 g of ethylene glycol dimethacrylate (EGDMA) were used to synthesize insulating fine particles with a size of 220 nm and a glass transition temperature (Tg) of 110°C.

[0129] <Example 5>

[0130] Conductive particles and an anisotropic conductive film were prepared in the same manner as in Example 1, except that 30 g of ethylene glycol dimethacrylate (EGDMA) was used to synthesize insulating fine particles having a size of 220 nm and a glass transition temperature (Tg) of 110°C.

[0131] <Example 6>

[0132] Conductive particles and an anisotropic conductive film were manufactured in the same manner as in Example 1, except that a 5 wt % solution in which the insulating fine particles of Examples 1 and 3 were mixed at a weight ratio of 5:5 was used.

[0133] <Example 7>

[0134] Conductive particles and an anisotropic conductive film were manufactured in the same manner as in Example 1, except that a 5 wt % solution in which the insulating fine particles of Examples 2 and 3 were mixed at a weight ratio of 5:5 was used.

[0135] <Example 8>

[0136] Conductive particles and an anisotropic conductive film were produced in the same manner as in Example 2 except that 20 wt % of the insulating fine particle dispersion based on the weight of the conductive particles was used in the insulating fine particle attaching step.

[0137] <Example 9>

[0138] Conductive particles and an anisotropic conductive film were produced in the same manner as in Example 2 except that the insulating fine particle dispersion was used in an amount of 5 wt % based on the weight of the conductive particles in the insulating fine particle attaching step.

[0139] <Example 10>

[0140] Conductive particles and an anisotropic conductive film were manufactured in the same manner as in Example 1, except that dodecane thiol was used as a surface treatment chemical during the surface treatment process.

[0141] <Comparative Examples 1 to 10>

[0142] By comparing the physical properties of the products after surface treatment, in Comparative Examples 1 to 10, the conductive particles with insulating particles attached were dried by a spray dryer, and the conductive particles and anisotropic conductive films were manufactured in the same manner as in Example 1.

[0143] Experimental Example 1

[0144] The anisotropic conductive films (ACFs) manufactured in Examples 1 to 10 and Comparative Examples 1 to 10 were observed using an optical microscope to measure the number of aggregated conductive particles. 2 The ACF of the area is used to measure the number of aggregated particles formed by the aggregation of more than 5 conductive particles. The number of aggregated particles is listed in Table 1 in units of parts per million (ppm).

[0145]

Table 1

[0146] Aggregation evaluation results before and after surface treatment

[0147]

[0148] Experimental Example 2

[0149] Optical photographs of the dispersion of the conductive particles in the anisotropic conductive film in Example 1 and Comparative Example 1 were taken, respectively. Figure 1 and Figure 2 As shown. It can be confirmed Figure 1 The conductive particles dispersed in Example 1 are Figure 2 The conductive particles of (Comparative Example 1) were dispersed without aggregation.

[0150] Experimental Example 3

[0151] A scanning electron microscope (SEM) photograph of the conductive particles with insulating particles attached in Example 1 is taken. Figure 3 shown.

[0152] The features, structures, effects, etc. listed in the above embodiments can be achieved by those skilled in the art through combinations or modifications of other embodiments. Therefore, the contents of these combinations and modifications should be interpreted as being included in the scope of the present invention.

Claims

1. A conductive particle, characterized in that: The conductive particles dispersed in a resin composition of an anisotropic connection material containing a binder resin and a solvent include: nuclear; a conductive layer disposed on the core and comprising a metal; Insulating particles connected to the conductive layer via a first substituent bonded to a metal of the conductive layer, and provided in a first region of the conductive layer; and A hydrophobic surface treatment layer connected to the conductive layer via a second substituent bonded to the metal of the conductive layer, and provided in the second region of the conductive layer; The first area does not overlap with the second area.

2. The conductive particle according to claim 1, characterized in that The height of the insulating particles is 100 to 300 nm.

3. The conductive particle according to claim 1, characterized in that The first substituent is at least one selected from the group consisting of an hetero group, an ether group, a carbonate group, and a hydroxyl group.

4. The conductive particle according to claim 1, characterized in that The second substituent is at least one selected from the group consisting of a thiol group, a phosphoric acid group, and a phosphoric acid ester group.

5. The conductive particle according to claim 1, characterized in that Bumps are also provided in the conductive layer.

6. The conductive particle according to claim 5, characterized in that At least one insulating particle is formed on the protrusion.

7. The conductive particle according to claim 5, characterized in that The surface treatment layer is formed on the protrusion.

8. The conductive particle according to claim 5, characterized in that The diameter of the insulating particles is greater than the height of the protrusions.

9. An anisotropic conductive material, characterized in that: As an anisotropic conductive film produced using the conductive particles according to any one of claims 1 to 8, When observed under an optical microscope, 2 The number of aggregated particles formed by aggregation of 5 or more of the conductive particles on an area is less than 0.2 ppm.

10. A method for producing conductive particles, characterized in that: include: Core provision step; a conductive layer forming step of forming a conductive layer with or without protrusions on the core; an insulating particle adhering step of adhering insulating particles to a first region of the conductive particle intermediate by mixing the conductive particle intermediate produced in the conductive layer forming step, a solution containing insulating particles having a first substituent, and a solvent; a surface treatment step of forming a surface treatment layer on a second region of the conductive layer different from the first region by mixing a surface treatment substance having a second substituent after the insulating particle adhering step; and A drying step is performed after the surface treatment step.

11. The method for producing conductive particles according to claim 10, wherein: In the conductive layer forming step, the conductive layer has a thickness of 80 nm to 400 nm.

12. The method for producing conductive particles according to claim 11, wherein: The drying step is performed at 100°C to 200°C.

13. The method for producing conductive particles according to claim 12, wherein: In the insulating fine particle adhering step, the insulating particles are adhered to 5% to 40% of the entire area of ​​the outer side surface of the conductive layer.